Knowledge and Proportion of COVID-19 Vaccination and Associated Factors Among Cancer Patients Attending Public Hospitals of Addis Ababa, Ethiopia, 2021: A Multicenter Study - Tadele Admasu F (Dove Medical Press, 2021)
Fitalew Tadele Admasu Department of Biomedical Sciences, College of Health Sciences, Debre Tabor University, Debre Tabor, EthiopiaCorrespondence: Fitalew Tadele AdmasuDepartment of Biomedical Sciences, College of Health Sciences, Debre Tabor University, PO Box: 272, Debre Tabor, EthiopiaTel +251 918290166Email fitalewtadele@gmail.comBackground: Cancer patients are classified as being at high risk of contracting COVID-19 infection, hospitalization, and death and were recommended to have early access to the limited COVID-19 vaccine. However, there are limited studies on the knowledge and acceptance of the COVID-19 vaccine among cancer patients. Therefore, this study aimed at assessing the awareness, readiness, and associated factors among cancer patients.Methods: Institution-based cross-sectional study was conducted on 422 cancer patients from May to August, 2021. A structured interviewer-administered questionnaire was used to collect primary data. A systematic random sampling technique was used to select study participants. Descriptive statistics and binary logistic regression followed by multivariable analysis were performed to investigate the independent association of factors with the outcome variable. Finally, statistical significance was declared at P < 0.05 using AOR and 95% CI.Results: From the 422 cancer patients who participated, 77 (18.2%) had a history of COVID-19 infection, and 224 (55%) believe that the cancer disease will not make them more vulnerable to be infected by COVID-19. Accordingly, younger age (18– 30 years) (AOR = 2.73: 95% CI: 0.18, 4.51), female (AOR = 6.4: 95% CI: 0.7, 13.8), having information about COVID-19 vaccine (AOR = 6.9: 95% CI: 3.1, 15.2), COVID-19 infection history (AOR = 6.0: 95% CI: 2.5, 11.8), duration since cancer diagnosis (≥ 10 years) (AOR= 6.2: 95% CI: 2.6, 14.7), and belief about the likelihood of dying of COVID-19 infection (AOR = 3.05: 95% CI: 1.03, 4.05) were the independent predictors of the likelihood of receiving COVID-19 vaccine among cancer patients.Conclusion: This study has found significant cancer patients with poor knowledge about the vaccine, and the percentage of both the first and second round of COVID-19 vaccination was small. Therefore, information communication with cancer patients and oncologists about the COVID-19 vaccine may help to decrease vaccine hesitancy.Keywords: COVID-19, vaccine, willingness, cancer, Ethiopia